Hybrid anaerobic reactor: Brewery wastewater and piggery effluent valorisation - Neves, André (2020)
ABSTRACT: A hybrid anaerobic reactor (HAR) operated to digest brewery wastewater, complemented with piggery effluent (60% and 40% v/v, respectively), under three hydraulic retention times: HRT: 5.7, 3.0 and 1.0 d. Along the first phase, the biogas of 0.9 LL− 1d− 1 evolved to 1.2 LL− 1d− 1 with a methane content of 77–78%. The HRT reduction to 3 days promoted the production until 2.1 LL− 1d− 1, with methane proportions of 79.5%. The operation with an even lower HRT (1 d) allowed to obtain a higher biogas (2.9 LL− 1d− 1, 79.5% CH4). HAR was successfully applied to the mixture digestion, even with a HRT as low as 1 day. Phenolic compounds with antioxidant capacity in effluent adds value, besides the supply of biogas/methane.